De la victime émissaire à la pensée symbolique - Jean-Jacques Vincensini (Carnets)
What place does René Girard occupy in the human sciences? Our answer shall start with his criticism of Freudian psychoanalysis, which leads him to consider violence as the « transcendental signifier » of desires and of every cultural expression. The consequences of this criticism are particularly obvious in René Girard's confrontation with Claude Lévi-Strauss. As Levi Strauss witnesses the characteristic structure of the « savage » or « symbolical » thought specific to each mythical or legendary group, he refuses the supremacy allowed to a specific code (such as sexuality or violence): the symbol is not related to an unchanging and « transcendant » signifier veiled by the text. We shall study this confrontation through an emblematic example drawn from medieval literature. The studied pattern « thinks » mimetic violence, corporal urges and the necessity to moderate them, in a specific symbolic and cultural perspective.31 janvier 2018